2008
DOI: 10.1515/iral.2008.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigating pragmatic language learning in foreign language classrooms

Abstract: A lot of research addressing learners' development of pragmatics has recently been conducted (Kasper and Schmidt 1996; Bardovi-Harlig, 2002; Kasper and Rose 2002). From this same approach, a review of theoretical perspectives on pragmatic learning and how they have been operationalised in interlanguage pragmatic research is presented. Second, by paying attention to studies on learning the speech act of requesting that have been conducted in the EFL classroom, the author addresses the issue of whether cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Grossi (2009) revealed that explicit classroom instruction can assist learners from different backgrounds even if more advanced learners may develop awareness without instruction. Other studies (Gaily, 2014;Gorjian and Pourkaram, 2018;Noonkong and Charttrakul, 2017;Rajabi, Azizifar and Gowhary, 2015;Soler, 2008) revealed that explicit instruction of pragmatic aspects had positive influences on students' metapragmatic awareness and pragmatic use of English. Additionally, others (Glaser, 2013;Muthusamy & Farashaiyan, 2016) revealed that inductive instruction is more useful and effective than deductive instruction to teach L2 pragmatics.…”
Section: Pragmaticsmentioning
confidence: 93%
See 1 more Smart Citation
“…Grossi (2009) revealed that explicit classroom instruction can assist learners from different backgrounds even if more advanced learners may develop awareness without instruction. Other studies (Gaily, 2014;Gorjian and Pourkaram, 2018;Noonkong and Charttrakul, 2017;Rajabi, Azizifar and Gowhary, 2015;Soler, 2008) revealed that explicit instruction of pragmatic aspects had positive influences on students' metapragmatic awareness and pragmatic use of English. Additionally, others (Glaser, 2013;Muthusamy & Farashaiyan, 2016) revealed that inductive instruction is more useful and effective than deductive instruction to teach L2 pragmatics.…”
Section: Pragmaticsmentioning
confidence: 93%
“…Finally, the study of Gorjian and Pourkaram (2018) asserted that using pragmatic tasks explicitly to teach speaking skill was effective in developing learners' speaking proficiency. Rueda (2006), Martínez-Flor and Soler (2007), Soler (2008), Glaser (2013), Bagheri (2015), Rafieyan (2015), Rajabi, Azizifar and Gowhary (2015), Muthusamy and Farashaiyan (2016), Noonkong and Charttrakul (2017), Gorjian and Pourkaram (2018) and Kaliska (2018) revealed that there are two kinds of interventions for instructing pragmatics: deductive (explicit) and inductive (implicit). Glaser (2013) explained that the deductive teaching involves providing students with metapragmatic information and strategies following this with exercises and activities to practice these rules.…”
Section: Pragmaticsmentioning
confidence: 99%
“…Several researchers (Alcón Soler, 2008;Ishihara & Cohen, 2010;Kasper & Rose, 2002;Timpe, 2013) have argued for merging the cognitive and socially oriented perspectives-or, as Kasper and Rose (2002) have called them, the intrapersonal and interpersonal perspectives. Ishihara and Cohen (2010), for instance, stated that they "view the learning of pragmatics not only as a cognitive process but also as a social phenomenon, looking into how L2 speakers construct and negotiate their identities" (Ishihara & Cohen, 2010, p. x).…”
Section: The Socially Oriented Perspectivementioning
confidence: 99%
“…Although a significant body of research has investigated EAL learners' development of pragmatic knowledge (Soler, 2008), explicit teaching of sociopragmatic knowledge has received comparatively scant attention (Bou-Franch & Garcés-Conejos, 2003), and this is even more the case for taboo language and swearing (Holster, 2005). Littlewood (1983) asserted that teachers should not ignore the role of language in expression of individuality, and from the perspective of the current study, instruction that does not acknowledge the functions and existence of taboo language:…”
Section: Taboo Language Language Teachers and Learnersmentioning
confidence: 99%